EFFECTS OF CLIMATE ON DEER BONE δ15N AND δ13C: LACK OF PRECIPITATION EFFECTS ON δ15N FOR ANIMALS CONSUMING LOW AMOUNTS OF C4 PLANTS - Cormie A.B.; Schwarcz H.P. (My University, 1996)
We have examined the relationship of bone collagen δ15N and δ13C to climatic variables, humidity, temperature, and amount of precipitation using fifty-nine specimens of North American white-tailed deer (Odocoileus virginianus) from forty-six different locations. In previous studies of African mammals there was a significant correlation between bone collagen δ15N and local amount of precipitation. Results presented here similarly show an increase in δ15N with decreasing amount of precipitation but only for 25% of the animals, namely those consuming more than 10% C4 plants. These animals also exhibited a significant correlation between δ13C and temperature which mirrors previous observations for grasses suggesting that these deer consume grasses during times of population and nutrient stress.In contrast, even in dry areas containing high proportions of C4 grasses, the majority of the deer had consumed low amounts of C4 plants and these deer did not have δ15N which correlate with amount of precipitation. Only when deer deviated from their normal feeding patterns by consuming C4 plants or grasses did their δ15N correlate with amount of rainfall. For these animals, consumption of C4 plants or grasses may signal conditions of water and nutrient stress. An increase in δ15N of bone collagen may result from combined effects from excretion of concentrated urine (to conserve water) and increased internal recycling of nitrogen (to conserve nitrogen).